Neutrophil Activation in Acute Hemorrhagic Fever With Renal Syndrome Is Mediated by Hantavirus-Infected Microvascular Endothelial Cells - Strandin, Tomas; Mäkelä, Satu; Mustonen, Jukka; Vaheri, Antti (Frontiers in Immunology, 2018)
Hantaviruses cause hemorrhagic fever with renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS) in humans. Both diseases are considered to be immunologically mediated but the exact pathological mechanisms are still poorly understood. Neutrophils are considered as the first line of defense against invading microbes but little is still known of their role in virus infections. We wanted to study the role of neutrophils in HFRS using blood and tissue samples obtained from Puumala hantavirus (PUUV)-infected patients. We found that neutrophil activation products myeloperoxidase and neutrophil elastase, together with interleukin-8 (the major neutrophil chemotactic factor in humans), are strongly elevated in blood of acute PUUV-HFRS and positively correlate with kidney dysfunction, the hallmark clinical finding of HFRS. These markers localized mainly in the tubulointerstitial space in the kidneys of PUUV-HFRS patients suggesting neutrophil activation to be a major likely component of the general immune response towards hantaviruses. We also observed increased levels of circulating extracellular histones at the acute stage of the disease supporting previous findings of neutrophil extracellular trap formation in PUUV-HFRS. Mechanistically, we did not find evidence for direct PUUV-mediated activation of neutrophils but instead primary blood microvascular endothelial cells acquired a pro-inflammatory phenotype and promoted neutrophil degranulation in response to PUUV infection in vitro. These results suggest that neutrophils are activated by hantavirus-infected endothelial cells and may contribute to the kidney pathology which determines the severity of HFRS.